The hunter, the stag, and the mother of animals: image, monument, and landscape in ancient North Asia - Jacobson-Tepfer, Esther (Oxford University Press, 2015)
"Jacobson-Tepfer explores the changing traditions of belief in pre-Bronze and Bronze Age North Asia, centering her argument on a female deity and her evolution until the early Iron Age"--Provided by publisher